2010
DOI: 10.1007/s10484-010-9130-1
|View full text |Cite
|
Sign up to set email alerts
|

First Non-Contingent Respiratory Biofeedback Placebo versus Contingent Biofeedback in Patients with Chronic Low Back Pain: A Randomized, Controlled, Double-Blind Trial

Abstract: Previous studies reported that respiratory feedback (RFB) aids in alleviating chronic pain. However, to date, this adjunct treatment has not been rigorously tested against non-contingent (placebo) feedback. Forty-two patients with chronic low back pain were randomized to either RFB or non-contingent RFB. Both groups performed a daily 30-min home training for 15 consecutive days. A respiratory associated relaxation index (RI) was measured. Pain levels and a somatosensory profile were assessed before and after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
3
33
0
1
Order By: Relevance
“…Both studies showed efficacy of biofeedback for improving symptoms of chronic back pain and headaches, respectively. (89,90) …”
Section: Meditation/mindfulnessmentioning
confidence: 99%
“…Both studies showed efficacy of biofeedback for improving symptoms of chronic back pain and headaches, respectively. (89,90) …”
Section: Meditation/mindfulnessmentioning
confidence: 99%
“…It has been suggested that resonance frequency breathing (i.e., the breathing frequency that causes the largest HR oscillation amplitude) may strengthen baroreflexes, thus improving the autonomic functioning (Vaschillo et al 2002;Lehrer et al 2003). HRV BF has shown to be useful in treating symptoms in various disorders characterized by aberration of the ANS (Wheat and Larkin 2010), including posttraumatic stress disorder (PTSD) (Zucker et al 2009), depression (Siepmann et al 2008) and heart disease (Nolan et al 2005) as well as musculoskeletal pain (Hasset et al 2007;Kapitza et al 2010). However, further controlled studies are needed on muscle pain.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large evidence base for effective outcomes in other conditions such as tensiontype headache, 19 chronic pain, 20 and anxiety, 29 biofeedback has been overlooked in interventions designed to improve mood, coping, and fatigue in MS. Promisingly, in this study, biofeedback was shown to be effective in reducing fatigue, stress, and anxiety. The biofeedback group also demonstrated improved control of breathing rate and muscle tension, indicating that they could be easily taught how to self-regulate these two physiological After controlling for baseline and normality, ANOVA showed a trend toward breathing rate difference between groups for breathing rate at t3 as follows: F 1,39 = 3.347, P = .07, h 2 = .083.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that improve perceived selfcontrol and coping strategies in MS are needed. [15][16][17][18] Biofeedback, an intervention that promotes better selfregulation, has been found to improve coping strategies in headache and chronic pain 19,20 and foster positive beliefs about self-control.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation